Effects of feed management on performance, carcass characteristics and meat quality of Boer goats - Silva, Emanuel Isaque Cordeiro da; Fontain, Eduarda Carvalho da Silva (Revista de Ciências Agroveterinárias, 2025)
Goat farming is one of the fastest growing activities in terms of quality of its products. In this scenario, the Boer breed is the most important for the goat meat industry worldwide as it specializes in the production of quality meat, where the animals are slaughtered early and with satisfactory zootechnical indexes. Considering this favorable scenario, it was decided to evaluate the quality characteristics of the carcass and meat of these animals; then, 20 Boer goats were housed and distributed in groups where one group received a diet based on hay ad libitum and fixed amounts of corn meal and soybean meal in compliance with the requirements of maintenance and weight gain; the other group was housed in different paddocks daily and received only the roughage present in the pasture. It was observed that the animals tended to present larger posterior cuts (loin and leg) with no significant difference between the feeding regimes. The animals fed with concentrate accumulated more subcutaneous fat compared to the animals under grazing. The meat of grazing animals showed higher glycolytic potential and shear force (FC), however, it had lower final pH than the meat of animals fed with concentrate. It was also possible to verify a ratio of fatty acids from intramuscular fat 4 times higher in the carcass of animals under concentrated regime in comparison to the carcass of animals under rotational grazing. With this study, it can be stated that, through the adopted feed management, the quality characteristics of the carcass and meat and, consequently, their organoleptic attributes, can be influenced, having effects on the goat meat market.